Abstract ID: 183 Advances in the FLUKA PET tools. (October 2017) - Augusto, Ricardo Santos; Cuccagna, Caterina; Kozlowska, Wioletta; Ortega, Pablo Garcia; Toufique, Yassine; Bouhali, Othmane; Ferrari, Alfredo; Vlachoudis, Vasilis
Abstract : In this work the new developments of FLUKA[1, 2] Positron Emission Tomography (PET) tools[3] are presented. FLUKA is a fully integrated Monte Carlo (MC) particle transport code, widely used for an extended range of applications, including medical physics. Recently FLUKA has provided the medical community with dedicated simulation tools for clinical applications, such as DICOM to voxel or PET simulation packages. PET is a well-established imaging technique in nuclear medicine and a promising method for clinical in vivo treatment verification in hadrontherapy. The application of clinically settled PET scanners to new irradiation environments such as hadrontherapy requires further experimental and theoretical research to which MC simulations could be applied. The FLUKA PET tools, besides including existing models from PET scanner manufacturers in its library, allows the configuration of new PET prototypes, thanks to its geometry framework supported by FLUKA GUI – Flair. Both the beam time structure and acquisition time can be specified by the user, allowing the correct reproduction of PET monitoring. Furthermore, different scoring routines allow an analysis on single and coincident events, as well as identification of parent isotopes generating annihilation events. Two image reconstruction codes are currently supported: the Filtered Back-Projection and the Maximum-Likelihood Expectation Maximization. Compatibility with other reconstruction frameworks is also possible. The FLUKA PET tools have been successfully tested for different detectors and scenarios, including conventional PET Quality Assurance and in-beam PET, either using as a source radioisotopes density maps, or simulating hadron beams interacting with complex targets, accounting for the various nuclear reactions. Finally, the results obtained so far confirm that the FLUKA PET tools are suitable to perform PET simulation studies in clinical environment.